A framework for the development and measurement of agile enterprise architecture - Mthupha, Bokang (Rhodes University, Faculty of Commerce, Department of Information Systems, 2012)
Enterprise architecture is the high-level design of the entire business, facilitated by enterprise architects. "Agile enterprise architecture" is the term used in enterprise architecture to describe an architecture that caters for future unknowns, enabling change to occur rapidly without undue resource utilization, yet in a controlled manner and with minimal adverse impact. Some enterprise architects still use outdated, rigid approaches to enterprise architecture which are incompatible with today"Ÿs business environment. In addition, there is limited research into methods that can be applied to measure the agility of enterprise architecture. The current environment is such that there is a need for a more agile approach to developing and measuring enterprise architecture. This work will lead to the creation of a Framework for The Development and Measurement of Agile Enterprise Architecture. In support of the main goal of the development of the framework, a literature review will be conducted focusing on the necessary sub-goals of the research. The first sub-goal of the literature review is to develop a comprehensive definition for enterprise architecture (referred to as EA), as well as discover how it is currently practiced. Thereafter, the literature review will investigate a comprehensive definition for agility and research why it is emerging as a critical topic. The next chapter of the literature review will research how agility fits within the context of EA, uncovering a comprehensive definition for agile EA and the best practices in agile EA development. The final chapter of the literature review will investigate suitable measurement techniques that can be used to assess the level of agility of EA. On completion of the literature review, a preliminary framework will be created using the most important contributions from the literature. An empirical study will be conducted to explore the definitions for EA, agility, agile EA, the methods to measure the agility of EA and the concepts for the development of agile EA summarised in the preliminary framework. Data analysis follows an interpretive and qualitative approach based on four case studies through interviews with systems experts in four South African organizations in one province. Each interviewee was interviewed once. The initial interview with a Principal Consultant on Enterprise Strategy Consulting at organisation # 1 formed the basis of an exploratory study; the results of which were used to refine the research instrument and preliminary framework. Thereafter, a more rigorous empirical study focused on interviews with the Chief Architect, Senior Manager in Advisory Services and an Enterprise Architect at organizations 2, 3 and 4 respectively was conducted. The research follows an inductive approach to capture the interpretive experiences of participants and develop theoretical propositions from them. Following the exploratory pilot study it became necessary to make changes to the preliminary framework and initial survey instrument created. Thereafter, the empirical study consisting of the remaining three cases was conducted to test the important aspects of the framework and literature definitions. The analysis of the results of the empirical study prompted further changes to the theoretical framework and definitions created. The interviews conducted with each of the organizations confirmed the factors for agile EA development as well as the effectiveness of the definitions created in the literature review. The research uncovered that the need for a more agile approach to developing EA and a way to measure the level of agility of EA has become more and more significant in organizations. This begins with a better understanding of EA, agility, how agility fits within the context of EA, as well as appropriate methods to measure agility.
Keywords: Management information systems -- Research; Industrial management -- Technological innovations -- Research; Industrial organization -- Technological innovations -- Research; System design